Beyond Political Skin Colonial to National Economies in Indonesia and Vietnam (1910s-1960s) - Thuỷ, Phạm Văn (Springer Nature Singapore : Imprint: Springer, 2019)
This book explains the dynamics behind the economic transformation from colonial era to post-independence period in Indonesia and Vietnam. It analyses the different policies of Vietnamese and Indonesian governments towards the economic legacies of colonialism remaining in the countries after independence. It also demonstrates that despite critical differences between the two nation-states, Vietnamese and Indonesian leadership were pursuing similar long-term goals, which is to obtain a truly independent national economy. The book discusses the way in which the Indonesian government attained complete economic control which resembled the socialist transformation of North Vietnam in the 1950s and the various means by which the government of South Vietnam concentrated economic power in its hands during the late 1950s and early 1960s. It also explores how the Indonesian government was determined to get rid of the economic legacy of Dutch colonialism by placing the entire economy under the strong state control and ownership, in accordance with the spirit of Guided Democracy and Guided Economy in the late 1950s and the early 1960s. This book is a point of reference for students, researchers and academics interested in a comparative analysis of the economic systems implemented by the colonial and fascist powers in Indonesia and Vietnam.